Uso de aplicativos como ferramenta pedagógica nas aulas de educação física escolar: uma revisão integrativa - Vieira, Pedro Henrique da Silva (Brasil, 2024)
In the contemporary context, characterized by the use of Digital Information and Communication Technologies (TDICs) in various areas of everyday life, mainly in the educational sphere. This study aims to investigate how the use of applications can help in School Physical Education classes, based on an integrative literature review. The databases selected were: Scielo, Scopus, Lilacs and CAPES journals. The main results emphasize the importance of including technological applications and resources in Physical Education classes, highlighting their relevance and impact on the school environment. In relation to pedagogical practice, applications are tools that can motivate students in classes and bring content closer to everyday life, offering a valuable alternative for theoretical and practical teaching in Physical Education classes. Not that it refers to teacher training, it is worrying that many of them do not feel ready to deal with digital technologies, even though they know that they are important to the process of teaching-learning. It emphasizes that public policies must be more closely linked and follow the agreement with Law No. 14,533/2023 of the National Digital Education Policy (PNED), with investment in devices such as computers, tablets, TVs and good quality internet being essential to supply the needs of students and teachers.